Budgetary Reform Implementation and Public Expenditure Efficiency in Nigeria - Nkeiruka Chinyere Forcha-Chigbo (JOURNAL OF ACCOUNTING AND FINANCIAL MANAGEMENT, 2026)
This study investigated the relationship between budgetary reform implementation and public expenditure efficiency in Nigeria, focusing on three key reforms: Budget Calendar Timeliness Adherence (BCTA), Program-Based Budgeting Coverage (PBBC), and Performance-Based Budgeting Share (PBBS). A quantitative research design was employed, utilizing secondary data from government financial reports and international institutions, covering the period from 2000 to 2024. The study utilized Ordinary Least Squares (OLS) regression analysis to examine the impact of these reforms on public expenditure efficiency, measured by Expenditure Deviation from Approved Budget (EDAB).The findings revealed that BCTA, PBBC, and PBBS all had significant relationships with expenditure efficiency. BCTA was found to be positively related to EDAB, suggesting that better adherence to the budget calendar reduced expenditure deviations. Similarly, PBBC had a significant positive impact on EDAB, indicating that expanding program based budgeting improved expenditure efficiency. Furthermore, PBBS demonstrated a significant negative relationship with EDAB, showing that a higher share of performance-based budgeting led to lower expenditure deviations and enhanced fiscal accountability. These results were explained through the lens of the Principal-Agent Theory and New Public Management (NPM) Theory. The Principal-Agent Theory emphasized that aligning the interests of public officials with government goals, through reforms such as BCTA, PBBC, and PBBS, reduced inefficiencies in public expenditure. The NPM Theory supported the findings by highlighting the importance of performance-based approaches in fostering accountability and efficiency in public sector budgeting. Based on these findings, the study recommended enhancing adherence to budget calendars, expanding the use of program-based budgeting, and increasing the share of performance-based budgeting in Nigeria. It also called for strengthened monitoring and evaluation mechanisms and capacity building for public officials. This research contributed valuable insights into the role of budgetary reforms in improving public expenditure efficiency in Nigeria, offering practical recommendations for fiscal policy enhancement.